Are subjective business performance measures justified?. Issue 5 (13th June 2016) - Vij, Sandeep; Bedi, Harpreet Singh
Abstract : Purpose: – The purpose of this paper is to operationalize the subjective measures of business performance and assessing their justification for use in place of objective measures of business performance. Design/methodology/approach: – The study is based on a sample survey of 171 companies listed on Bombay Stock Exchange, India. A cross-sectional descriptive research design has been used. Exploratory factor analysis was used to assess the factor structure and dimensionality of objective and subjective measures of business performance. The psychometric properties of these measures and their interrelationship have been assessed through confirmatory factor analysis. Findings: – The study finds a strong positive correlation between subjective business performance and objective business performance. The study finds it justified to use the subjective measures of business performance. Research limitations/implications: – Response bias may have crept in because of self-reported measure used for the study. Future researchers may cross-verify the subjective perception of respondents with data available from the records of the firms. Second, the study focuses only on financial and operational indicators of performance. The future studies may widen the scope of business performance by incorporating the interests of other stakeholders like suppliers, government, environment and society in general. Practical implications: – The strategy researchers confronting the challenge of adopting appropriate measures of business performance can use either or both of subjective and objective performance measures, as suggested in this study. The study has suggestions for strategic decision makers regarding measurement of business performance in terms of financial as well as operational indicators. Originality/value: – The study operationalizes and validates two measures of performance, namely, subjective business performance and objective business performance. The study contributes to the strategic management literature by providing evidence for association between objective and subjective measures of performance.